BRIEF DESCRIPTION OF THE RESTORATION METHOD OF A VECTOR VELOCITY FIELD IN GASEOUS DISKS OF SPIRAL GALAXIES - Lyakhovich, V. V. (Одеські астрономічні публікації, 2017)
This work is the brief description of the restoration method of a vector velocity field in gaseous disks of spiral galaxies from observed line-of-sight velocities (more detailed description see Lyakhovich et al., Astron.Zn. 1997).